On the primacy of χωριστόν in the Aristotelian substance. Alexander’s commentary on Metaphysics V 8, 1017b 23-26 - Abbate, Giampaolo (Estudios de Filosofía, 2009)
This paper discusses Alexander’s commentary on Aristotle’s Metaphysics V.8 1017b23-26. There Aristotle maintains that substance is said in two ways: (i) the ultimate substrate, and (ii) the structure and form of each thing. Regarding the first meaning, the commentator properly makes emphasizes upon the fact that there is a perfect biunivocity between being substance and being substratum. This biunivocity, Abbate suggests, can be seen in the three entities that, according to Aristotle himself, since the of the Categories, a formula rewritten by Alexander as, can be called, in increasing order, matter, compound, and form. In fact, these entities show how being the ultimate substratum means not to be predicated of anything, a character that form, called by Alexander, is realized completely when it is entirely immaterial, insofar as it is not constituted by reference of one thing to another, let alone what its substratum is, that is, form as essence. Regarding the second meaning, the commentator seems to individualize three different meanings, according to which form can be called 1) it can be only, as a natural form which is immanent to bodies; 2) as a simple, that is, separated, in a passive sense, from matter, to which it is constitutively linked. This is the reason why form cannot subsist separately, if not virtually; as an eternal form of divine bodies, not subsisting in relation to any substratum, since it is not according to the last acception, the of form as a divine mover indicates a complete separation: both the individuality of a first substance as the trascendence as a pure form in actuality. It is a supre-sensible substance, which is separated as much as is the first mover. Therefore, Abbate concludes claiming Alexander authorizes us to think that the is the first character, that is, the character which more than any other accepts the distinction between that which is substance, and all that which is not substance, if it is true that the higher substances, the immaterial ones, are distinguished from the material substances in carrying this character to the maximum ful llment.